P101 Structured Holistic Nursing Assessment (HNA) in Buckinghamshire Healthcare Trust (BHT) for lung cancer & mesothelioma patients: process and findings. (15th November 2016) - Mowforth, J; Steiner, H; Prasad, A
Abstract : Aim: Lung cancer and mesothelioma patients have complex needs. Without a structured process of screening and assessment these can go undetected. Structured screening and assessment needs considered planning. Our experience of screening and assessment of the holistic needs for lung cancer and mesothelioma patients in BHT is described. Method: All BHT lung cancer and mesothelioma patients are invited to be screened post diagnosis using the Distress Thermometer and Needs checklist (Brennan et al 2012). 1 Participation rates vary between 55–65% and since 2013, 467 patients have been contacted with 265 patients participating. A database stores all HNA activity. This includes individual overall numerical score for distress (0–10), a breakdown of categories of need including physical, emotional, practical, social and spiritual. It also records specific aspects of distress within each category and where specified the top four aspects of need. Results: Of the 265 respondents, 196 (74%) recorded physical problems, 145 (54%) recorded emotional issues with worry, fear, sadness and depression sited as the top four aspects. In addition 63 (24%) reported practical problems e.g. money and transport, 53 (20%) family problems, and 32 (12%) spiritual concerns. Overall tiredness, breathing, getting around and worry are the top four needs recorded by our patients. Of all patients screened to date a third score Distress above 5, these patients are prioritised for a nurse led clinic. Conclusion: Through screening issues often not disclosed in doctor led clinics are identified and addressed leading to involvement of other professionals and services. Screening patients away from the clinical setting enables greater disclosure, prevents bias or influence on scoring and allows complex needs that might go undetected to be explored. The process enables care to be patient focused and proactive in managing complex needs before crisis events occur. Reference: Brennan J, et al . Refinement of the distress management problem list as the basis for a holistic therapeutic conversation among UK patients with cancer. Psycho-Oncology 2012;21 :1346–56.